Strategi Adaptasi Petani Minyak Kayu Putih Sebagai Dampak Pandemi Covid-19 - Muhamad Chairul Umanailo (Jurnal Ilmu Lingkungan, 2023)
Eucalyptus oil is a superior regional commodity in Buru Regency. In addition to the relatively high selling price, oil derived from the eucalyptus plant is needed by various industrial sectors to be used as an essential ingredient for medicine. However, when we examine the daily lives of eucalyptus oil farmers, we will find that the economic situation is quite worrying, and the socio-economic environment lags behind the workers in other sectors. If natural resources are abundant, eucalyptus oil workers should be able to have a decent life, especially amid the Covid-19 pandemic, which severely limits the social and economic space of workers. This study uses a phenomenological approach, the determination of informants using a purposive sampling technique based on predetermined criteria and determined based on the research objectives. Field findings show that farmers use physical adaptation strategies to meet production targets, negatively impacting labor and land sustainability. Excessive time and work patterns result in the emergence of physical insecurity among farmers, as well as land degradation, which endangers the survival of farmers. We propose that intensive and constant rehabilitation of production can reduce the detrimental impact of the physical approach of eucalyptus oil farmers during the pandemic, ensuring the sustainability of farmers and land.Keywords: Adaptation; Land, Farmers; Strategy